2019
DOI: 10.1002/hbm.24706
|View full text |Cite
|
Sign up to set email alerts
|

A multiparametric analysis of white matter maturation during late childhood and adolescence

Abstract: White matter development has been well described using diffusion tensor imaging (DTI), but the microstructural processes driving development remain unclear due to methodological limitations. Here, using neurite orientation dispersion and density imaging (NODDI), inhomogeneous magnetization transfer (ihMT), and multicomponent driven equilibrium single‐pulse observation of T1/T2 (mcDESPOT), we describe white matter development at the microstructural level in a longitudinal cohort of healthy 6–15 year olds. We ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 63 publications
8
62
4
Order By: Relevance
“…Age-related trends tended to be similar between left and right hemispheres, suggesting that at the macro-scale, brain development is similar between hemispheres. This is in contrast to investigations of individual microstructural features, where increases in VF m were shown to be largely left-lateralized during adolescence [57]. PC2 findings may be driven by NDI, as NDI has been previously shown to be age-sensitive and increases bilaterally throughout adolescence [57][58][59].…”
Section: Bayes Factor Analysiscontrasting
confidence: 86%
See 1 more Smart Citation
“…Age-related trends tended to be similar between left and right hemispheres, suggesting that at the macro-scale, brain development is similar between hemispheres. This is in contrast to investigations of individual microstructural features, where increases in VF m were shown to be largely left-lateralized during adolescence [57]. PC2 findings may be driven by NDI, as NDI has been previously shown to be age-sensitive and increases bilaterally throughout adolescence [57][58][59].…”
Section: Bayes Factor Analysiscontrasting
confidence: 86%
“…This is in contrast to investigations of individual microstructural features, where increases in VF m were shown to be largely left-lateralized during adolescence [57]. PC2 findings may be driven by NDI, as NDI has been previously shown to be age-sensitive and increases bilaterally throughout adolescence [57][58][59]. One relationship between PC1 and age remained in the left arcuate following multiple comparisons.…”
Section: Bayes Factor Analysiscontrasting
confidence: 79%
“…However, MT measures may also be sensitive to the effects of neuroinflammation or oedema (Gareau, Rutt, Karlik, & Mitchell, ; Stanisz, Webb, Munro, Pun, & Midha, ) and as such remain an imperfect measure of myelin. Future research might usefully address the specificity of our longitudinal findings to myelination by comparing MT saturation effects with other white matter microstructure metrics, an approach adopted in recent work in studies of late childhood and early adolescence, albeit reports on cross‐sectional and not longitudinal data (Geeraert, Lebel, & Lebel, ; Moura et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…62 Age-related increases of ND were also reported during late childhood and adolescence, suggesting axonal packing in this term. 63 For adults, Nazeri and colleagues 64 revealed age-related OD decreases in frontoparietal regions and increases in the hippocampus, as well as a relationship with executive function. Ota et al 65 also reported age-related changes in healthy adults in terms of NODDI and DTI/DKI parameters.…”
Section: Brain Developmentmentioning
confidence: 99%